2019
DOI: 10.22158/rhs.v4n3p191
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Physical Activity among Jordanian University Students

Abstract: Study Purpose: The purposes of this study were to examine the relationships between university students’ physical activity, self-efficacy and perceived benefits and barriers to exercise, and to identify predictors of physical activity among university students.Methods: A cross-sectional design was used in this study. A translated version of Exercise Benefits/Barriers Scale and Exercise Self-efficacy Scale were used to collect study data. A convenience sample of 517 university students participated in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…About 51.9% of all students who participated in the present study did not reach the IPAQ recommendations for physical activity ( IPAQ Research Committee, 2005 ). Similarly, a prior Jordanian survey found that less than 50% of university students did not reach the physical activity subscale of the Health-Promoting Lifestyle Profile II (HPLP II) ( Hamdan & Shaheen, 2019 ). According to a Chinese survey, the level of physical activity in Chinese students does not align with the levels recommended by IPAQ ( Liu & Dai, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…About 51.9% of all students who participated in the present study did not reach the IPAQ recommendations for physical activity ( IPAQ Research Committee, 2005 ). Similarly, a prior Jordanian survey found that less than 50% of university students did not reach the physical activity subscale of the Health-Promoting Lifestyle Profile II (HPLP II) ( Hamdan & Shaheen, 2019 ). According to a Chinese survey, the level of physical activity in Chinese students does not align with the levels recommended by IPAQ ( Liu & Dai, 2017 ).…”
Section: Discussionmentioning
confidence: 99%